The social revolution in Costa Rica Social Reform, Catholic Church, Communist Party and Civil War of 1948 - Barahona Riera, Macarena (2016)
The civil war in Costa Rica was the scene of the most violent confrontation of classes given Costa Rican society. Scenario of violence physical, political, financial and ideological. The vanquished were victims of persecution, exile and social and political exclusion for decades. Espionage and regional partnerships were key to the triumph of the victorious forces. Presents a reflection on the main actors of the clash of classes, political, ideological and military. The growing season of social, trade union organizations of major triumphs of social legislation and progressive social programs, which were confronted by opposition groups allied to Central American pacts. The vanquished militarily surrender under a Pact being ignored. And it reflects on the need to return to primary sources to better understand these events. Clarify the conspiracies and political and international pressure, the role of Mexico in espionage, is still pending to investigate other issues, refugees, prison, the dead and the missing from this period.